The healthcare competence of primary school teachers: the notion and structure (Pedagogy of Higher and Secondary Education, 2013)
Lando O. A. The healthcare competence of primary school teachers: the notion and structure.The article is devoted to the problem of healthcare competence of primary school teachers. The notion and structure of healthcare competence of future primary school teachers are defined. The necessity of the realized attitude towards health and healthy lifestyle is researched.
Keywords: competence; competency; healthcare